Intention to breastfeed and awareness of health recommendations: findings from first-time mothers in southwest Sydney, Australia - Baur Louise A; Wen Li; Rissel Chris; Alperstein Garth; Simpson Judy M (BMC, 2009)
Abstract Background In 2001, the World Health Organisation (WHO) recommended exclusive breastfeeding for the first six months of life. The objectives of this study are to assess awareness of the WHO recommendation among first-time mothers (women at 24 to 34 weeks of pregnancy) and to explore the relationship between this awareness and mothers' intention to exclusively breastfeed for six months. Methods This study was part of the Healthy Beginnings Trial (HBT) conducted in southwest Sydney, Australia. We analysed cross-sectional baseline data of the trial conducted in 2008, including 409 first-time mothers at 24 to 34 weeks of pregnancy. The mothers' awareness of the recommended duration of exclusive breastfeeding and their intention to meet the recommendation were assessed through face-to-face interviews. Socio-demographic data were also collected. Factors associated with awareness of the recommendation, or the intention to meet the recommendation, were determined by logistic regression modeling. Log-binomial regression was used to calculate adjusted risk ratios (ARR). Results Sixty-one per cent of mothers knew the WHO recommendation of exclusive breastfeeding for six months. Only 42% of all mothers intended to meet the recommendation (breastfeed exclusively for six months). Among the mothers who knew the recommendation, 61% intended to meet the recommendation, compared to only 11% among those mothers who were not aware of the recommendation. The only factor associated with awareness of the recommendation was mother's level of education. Mothers who had a tertiary education were 1.5 times more likely to be aware of the recommendation than those who had school certificate or less (ARR adjusted for age 1.45, 95% CI 1.08, 1.94, p = 0.02). Mothers who were aware of the recommendation were 5.6 times more likely to intend to breastfeed exclusively to six months (ARR adjusted for employment status 5.61, 95% CI 3.53, 8.90, p < 0.001). Conclusion Awareness of the recommendation to breastfeed exclusively for six months is independently associated with the intention to meet this recommendation. A substantial number of mothers were not aware of the recommendation, particularly among those with low levels of education, which is of concern in relation to promoting breastfeeding. Improving mothers' awareness of the recommendation could lead to increased maternal intention to exclusively breastfeed for six months. However, whether this intention could be transferred into practice remains to be tested. Trial Registration HBT is registered with the Australian Clinical Trial Registry (ACTRNO12607000168459)